TAXONOMIC REMARKS ON TWO SPECIES OF THE GENUS SCYLLA DE HAAN (PORTUNIDAE : BRACHYURA) FROM PULICAT LAKE - Joel, D Rajasingh; Raj, P J Sanjeeva (Indian Journal of Fisheries, 2011)
Two species of decapod genus Scylla de Haan 1833 from Pulicat lake havebeen examined with reference to the more variable characters and are confirmed astwo valid species. A key for their identification and figures are provided..